2023
DOI: 10.3390/ijms24087439
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of TB/FLU-04L—An Intranasal Influenza Vector-Based Boost Vaccine against Tuberculosis

Abstract: Tuberculosis is a major global threat to human health. Since the widely used BCG vaccine is poorly effective in adults, there is a demand for the development of a new type of boost tuberculosis vaccine. We designed a novel intranasal tuberculosis vaccine candidate, TB/FLU-04L, which is based on an attenuated influenza A virus vector encoding two mycobacterium antigens, Ag85A and ESAT-6. As tuberculosis is an airborne disease, the ability to induce mucosal immunity is one of the potential advantages of influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Similar studies assessing the safety of recombinant influenza viruses expressing M. tuberculosis’ proteins ESAT-6 and Ag-85 in laboratory animals such as mice and guinea pigs have proved them to be completely safe. They have also demonstrated that animals immunised with recombinant influenza viruses developed a T-cell immune response and a level of protection that was not inferior to those induced by commercial BCG vaccines [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies assessing the safety of recombinant influenza viruses expressing M. tuberculosis’ proteins ESAT-6 and Ag-85 in laboratory animals such as mice and guinea pigs have proved them to be completely safe. They have also demonstrated that animals immunised with recombinant influenza viruses developed a T-cell immune response and a level of protection that was not inferior to those induced by commercial BCG vaccines [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…TB/FLU-04L is another viral vector vaccine based on the replication-deficient influenza virus expressing two M.tb antigens, Ag85A and ESAT-6 [ 6 ]. Preclinical studies in mice showed induction of strong T helper 1 (Th1)-type immune response and reduced regulatory T cells (Treg cell), when administered as booster to BCG [ 71 ]. It is in Phase I clinical trials [ 4 ].…”
Section: Description Of Various Vaccine Candidates Designed Against Tbmentioning
confidence: 99%
“…When administered as part of a "prime-boost" strategy, a single immunization with TB/FLU-04L vaccine in mice demonstrated comparable levels of protection to BCG. It dramatically improved the protective effect of BCG [77] Neonatal and adult mice were used to test the replication-deficient lymphocytic choriomeningitis virus (rLCMV)-based vaccine vector producing Mtb antigens Ag85B and TB10.4 (Ag85B-TB10.4). After delivery, it was noted that this vaccine could produce heterogeneous CD4 + , and CD8 + T-cell populations, and lung damage when infected with Mtb was reduced.…”
Section: Tb/flu-04lmentioning
confidence: 99%